Prospect Theory and Inflation Perceptions - An Empirical Assessment - Lena Vogel; Jan-Oliver Menz; Ulrich Fritsche (Hamburg University, Department Economics and Politics, 2009)
Building on the hypotheses of loss aversion with respect to price increases and availability of frequently bought goods, Brachinger (2006,2008) constructs an alternative index of perceived inflation (IPI), which can reproduce the jump in the measure for perceived inflation after the Euro introduction in Germany that was not observable in standard HICP inflation. We test the hypotheses of Prospect Theory with regard to households inflation perceptions underlying Brachingers IPI in a panel estimation for 12 European countries. There is evidence that perceptions react more strongly to losses in inflation than to gains before the Euro cash changeover, but not afterwards. Moreover, we find empirical support for the availability hypothesis, stating that frequently bought goods have a stronger influence on inflation perceptions than the overall price index.
Keywords: D81; D82; E52; C33; 330; Inflation Perceptions; Prospect Theory; Dynamic Panel